Mantas de nanofibras de gelatina/policaprolactona para liberação tópica de diclofenaco de potássio visando potencial ação antiinflamatória - Gabriella Onila do Nascimento Soares (2021)
Controlled release systems for topical use have been widely studied as an alternative to conventional administration and seek to provide innovative solutions for many applications as well as treatments. Nanofiberbased drug delivery technologies are highlighted in this scenario and the electrospinning of polymer blends, in particular, is a modern way to create biocompatible materials for biomedical applications. Adverse effects in the circulatory system, gastrointestinal tract, kidneys, and liver are commonly related to the conventional oral administration of diclofenac potassium (DP), therefore, the study of a new route of administration based on electrospun nanofibers of Gelatin / Polycaprolactone loaded with DP is a biomaterial with potential topical application of DP, aiming the patient's life quality improvement. The work describes the development of Gelatin/Polycaprolactone nanofibers incorporated with DP (5, 10, and 15 % m/m) using the electrospinning method. SEMEDS evidenced success in the drug incorporation, while FTIR and DSC indicated a possible interaction between gelatin and DP. The in vitro biodegradation study showed gelatin dissolution and the in vitro release analysis revealed a dependence of the release profile on the DP concentration and temperature. The in vitro permeation study using porcine skin (nanofibers with 10 % m/m of DP) and identified the presence of the drug in the epidermis and dermis, indicating the dermal targeting of the DP, which can improve the pharmacological effect of this drug.